2014
DOI: 10.1021/ac403384n
|View full text |Cite
|
Sign up to set email alerts
|

X13CMS: Global Tracking of Isotopic Labels in Untargeted Metabolomics

Abstract: Studies of isotopically labeled compounds have been fundamental to understanding metabolic pathways and fluxes. They have traditionally, however, been used in conjunction with targeted analyses that identify and quantify a limited number of labeled downstream metabolites. Here we describe an alternative workflow that leverages recent advances in untargeted metabolomic technologies to track the fates of isotopically labeled metabolites in a global, unbiased manner. This untargeted approach can be applied to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
235
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(238 citation statements)
references
References 37 publications
3
235
0
Order By: Relevance
“…The summed ion count of each of these acyl-CoA groups, representing the total abundance of a species in all of its observed labeled forms, was markedly increased in HMGCS2-deficient livers, suggesting increased flux through the DNL pathway ( Figure 5, C and D). To confirm that these identified acyl-CoA species were not differentially labeled by [ 13 C]pyruvate, bioinformatics analysis using software that we recently developed (40) revealed that these compounds were not labeled differently in ketogenesis-insufficient animals compared with those in controls, again supporting that augmented acyl-CoA pools cannot simply be attributed to increased labeling, but instead indicate increased pool sizes. Moreover, terminal oxidation of [ (41).…”
Section: 8mentioning
confidence: 92%
“…The summed ion count of each of these acyl-CoA groups, representing the total abundance of a species in all of its observed labeled forms, was markedly increased in HMGCS2-deficient livers, suggesting increased flux through the DNL pathway ( Figure 5, C and D). To confirm that these identified acyl-CoA species were not differentially labeled by [ 13 C]pyruvate, bioinformatics analysis using software that we recently developed (40) revealed that these compounds were not labeled differently in ketogenesis-insufficient animals compared with those in controls, again supporting that augmented acyl-CoA pools cannot simply be attributed to increased labeling, but instead indicate increased pool sizes. Moreover, terminal oxidation of [ (41).…”
Section: 8mentioning
confidence: 92%
“…Once molecules that differentiate the 2 populations have been identified, a targeted approach can be used to further characterize the utility of monitoring changes in the putative biomarkers. One particularly novel approach to metabolomics is the use of stable isotopes to trace metabolic fate of energy sources in diseased and healthy cells (24 ).…”
Section: Reviewsmentioning
confidence: 99%
“…Such information can also be ob-tained from NTFD by analyzing specific mass spectrometric fragments [9] or combinations thereof [25]. MzMatch-ISO [18] and X 13 CMS [14] are both R packages that allow for the non-targeted determination of MIDs and can be regarded as the LC-MS equivalents of NTFD.…”
Section: Overviewmentioning
confidence: 99%
“…Although many metabolic pathways are well described and known since many years, new reactions are continuously being identified, [10,11] underlining the necessity for a global detection of isotopic enrichment. Recently, several tools for the non-targeted detection of isotopic enrichment in mass spectrometric data have been developed [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%